Multiculturalism in the British Commonwealth : comparative perspectives on theory and practice - Ashcroft, Richard T., 1975-; Bevir, Mark (University of California Press, 2017)
"Since World War II, multiculturalism has risen steadily to prominence, but in recent years this growing consensus has been fractured. Multiculturalism in the British Commonwealth examines responses to cultural diversity across the postwar Commonwealth, situating modern multiculturalism in its national, international, and historical contexts. Bringing together practitioners from across the humanities and social sciences to explore the legal, political, and philosophical issues involved, these essays address common questions: What is postwar multiculturalism, and why did it come about? Covering a range of countries as diverse as India, Nigeria, Trinidad, Malaysia, and Singapore, Britain, Canada, Australia, and New Zealand, this volume traces the historical roots of contemporary dilemmas back to the intertwined legacies of imperialism and liberalism. In so doing, it demonstrates that multiculturalism has implications that stretch far beyond its current formulations in public and academic discourse"--Provided by publisher.